Interplay between Lignans and Gut Microbiota: Nutritional, Functional and Methodological Aspects - Baldi, Simone; Tristán Asensi, Marta; Pallecchi, Marco; Sofi, Francesco; Bartolucci, Gianluca; Amedei, Amedeo (Molecules (Basel, Switzerland), 2023)
Lignans are non-flavonoid polyphenols present in a wide range of foods frequently consumed in the Western world, such as seeds, vegetables and fruits, and beverages such as coffee, tea and wine. In particular, the human gut microbiota (GM) can convert dietary lignans into biologically active compounds, especially enterolignans (i.e., enterolactone and enterodiol), which play anti-inflammatory and anti-oxidant roles, act as estrogen receptor activators and modulate gene expression and/or enzyme activity. Interestingly, recent evidence documenting those dietary interventions involving foods enriched in lignans have shown beneficial and protective effects on various human pathologies, including colorectal and breast cancer and cardiovascular diseases. However, considering that more factors (e.g., diet, food transit time and intestinal redox state) can modulate the lignans bioactivation by GM, there are usually remarkable inter-individual differences in urine, fecal and blood concentrations of enterolignans; hence, precise and validated analytical methods, especially gas/liquid chromatography coupled to mass spectrometry, are needed for their accurate quantification. Therefore, this review aims to summarize the beneficial roles of enterolignans, their interaction with GM and the new methodological approaches developed for their evaluation in different biological samples, since they could be considered future promising nutraceuticals for the prevention of human chronic disorders.